Correlação entre equilíbrio de membros inferiores e flexibilidade em jovens atletas de futebol feminino - Silva, Yuri Rolim Lopes (2024)
This study seeks to verify whether there is a correlation between balance and flexibility in young female soccer players. The samplecomprised 20 female soccer athletes, divided into 2 groups: the Movement Group (GMOV) with 13 athletes, and the Flexibility Group (GFLEX) with 7 athletes, all of them from the U15 and 17 categories, respectively. Data were collected over 2 days: in the first, height and body mass were measured, and flexibility tests using a fleximeter and the Star Excursion Balance Test wereconducted; on the second day, step-down, step-up and unilateral squats were performed. In the GFLEX group, the results showed nocorrelations between the Star Excursion Balance Test and flexibility. The GMOV group exhibited a moderate negative correlation between hip misalignment angle and knee misalignment angle in the step-up test (r=-571; p<0.05), and a moderate positivecorrelation between left knee misalignment angle in the unilateral squat and step-down test (r=0.594; p<0.05). There was no correlation between balance and lower extremity flexibility in young female soccer players for the GFLEX group, while the GMOVgroup showed a relationship between the unilateral squat and step-down tests in terms of knee misalignment, as well as hip and knee misalignment in the step-up test.